Análisis de evaluación de factores internos del departamento de distribución de energía de la Corporación Nacional De Electricidad, Empresa Pública (Cnel Ep)- Los Ríos. - Guerrero Delgado, Cesar Vicente (2022)
The analysis of internal factors is a fundamental requirement for companies, since it supports organizational management, ensuring that processes are carried out in a transparent and safe manner. In addition, it is important because through this analysis both the strengths and weaknesses of the company are established in order to take corrective actions in case there are problems that may affect its activities; that is, it contributes to determine more efficient and effective work methodologies. The objective of this case study was to conduct an evaluation analysis of internal factors in the Distribution Area of the Corporación Nacional de Electricidad EP - Los Ríos, with the intention of identifying the main weaknesses of the institution in the aforementioned unit. The methodology implemented was a non-experimental design with a qualitative approach, supported by the empirical method, since only the interview technique was used for data collection. A field research was also carried out, where an interview guide was used, directed to the collaborators who manage the Distribution Area. The results of the study showed that one of the main drawbacks of public sector institutions is the weak administrative capacity of their managers. The research concluded that the institution does not develop evaluation processes of internal factors; therefore, it is impossible to know the main weaknesses it has, in order to establish continuous improvement strategies that promote organizational development and strengthen the corporate image.